Imperien, Nationen, Regionen Imperiale Konzeptionen in Deutschland und Russland zu Beginn des 20. Jahrhunderts - Wirsching, Andreas; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
This eighth volume of the Communications of the Joint Research Committee on the Contemporary History of German-Russian Relations documents the 2016 colloquium held in Moscow devoted to the theme "Empires, Nations, and Regions: Conceptions of Empire in Germany and Russia at the beginning of the 20th Century."